External prestressing technique for reinforced concrete member strengthening: A review study - Abbas, Aamer Najim; Hamood, Mohammed J.; Abdulsahib, Wael Shawky (AIP conference proceedings, 2024)
External prestressing was originally developed as a way to strengthen bridges. To improve the durability of new structures, external prestressing technique was also used. Externally prestressed concrete bridges are gaining popularity due to their advantages, due to easier concrete casting of new members, use of smaller cross section, ease of execution and replacement of reinforcement, low frictional losses, and economy. External prestressing is the use of non-bonded tendons (outside a member) to increase the strength of a structure and anchored at the edges to provide extra support to a structure, sometimes with one or more deviators along the length of the member. This reinforcement is helpful in strengthening structural members to improve their ability to bear the load. This paper gives an overview of the literature on this subject, also a reviewing the first research interested in external pre-stressing. External prestressing has both advantages and disadvantages, the benefits include increased strength and durability, while the disadvantages include the potential for environmental damage and increased costs. In this paper, the proper ways to overcome the problems of external prestressing were also suggested and discussed. From this review, the conclusions are that the external Prestressing provides the structure and makes the design reliable.